Pembuatan Naskah Cerita Teater Pada Kelompok Kesenian Bantengan Turangga Jaya Desa Wiyu Kecamatan Pacet Kabupaten Mojokerto - Koko Hari Pramono; Indar Sabri (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2023)
The performing arts of traditional theater in the community, especially in the Mojokerto area, there are many art groups that still exist. This is evidenced by the large number of art groups spread across various regions in the regency and city of Mojokerto. One of the iconic arts that is the pride of Mojokerto residents is Bantengan art, this art has its own prestige for every Mojokerto resident. Bantengan art is almost owned by every village, usually between one village and another village competing with each other to make the banteng arts group they protect better than the others. Because of that, the banteng arts in the Mojokerto region are developing and are in demand by the younger generation. Besides that, the bullfighting art certainly has its own challenges in its conservation efforts, this is because of the challenges of modernization and technological developments. In other words, the banteng that exist in Mojokerto are able to survive because each region has its own prestige to preserve and make the banteng arts group superior to other groups. However, specifically in the community service carried out by the writer in the village of Wiyu, Pacet District, Mojokerto Regency, he found that the storyline of the banteng storyline had not been conceptualized into a traditional theatrical performance. Thus the author goes directly into the field to collect data in an effort to write a dramatic story about the bullfighting scene with a simpler packaging but conveys the meaning and message of the story.